-8x-5-1x=15x-17-6x

Simple and best practice solution for -8x-5-1x=15x-17-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-5-1x=15x-17-6x equation:



-8x-5-1x=15x-17-6x
We move all terms to the left:
-8x-5-1x-(15x-17-6x)=0
We add all the numbers together, and all the variables
-8x-1x-(9x-17)-5=0
We add all the numbers together, and all the variables
-9x-(9x-17)-5=0
We get rid of parentheses
-9x-9x+17-5=0
We add all the numbers together, and all the variables
-18x+12=0
We move all terms containing x to the left, all other terms to the right
-18x=-12
x=-12/-18
x=2/3

You can always share this solution

See similar equations:

| 42x^2-11=14 | | 4x+6=x+45 | | 5+4(x-1)=2x-9) | | 1.35-x=-0.25 | | 8x+48+x=93 | | 17x+20=12x+60 | | x*1.15=97500 | | 3(x+2)-5=27 | | 7x-7+8x-8=90 | | 97500=x+(1.15x) | | 42x^-11=14 | | 6x-38=5x-29 | | 2x-19=-1 | | 4/9(9-27/16)=x | | x=(1.15x)=97500 | | 6x+57-24=75 | | .6x+3=5x?8 | | 97500=x+1.15x | | 6x+57-24=6 | | x=74.93+0.15(x) | | x+.13x=75 | | 3x+7-10=6 | | 2x-1÷3=9 | | 9-3m=-m-(4m+1) | | N-5=3n+5 | | 70x+80x=225 | | 5-(4x+8)=5-4x-8 | | 3x+5+2x=5(2+x) | | 121/x=55/5 | | -1.7(2x-5.2=34 | | 8y-10-4y+7=0 | | x^2-27x+139=0 |

Equations solver categories